Neurophysiological mechanisms of circadian cognitive control in RLS patients - an EEG source localization study - Zhang, Rui; Brandt, Moritz D; Schrempf, Wiebke; Beste, Christian; Stock, Ann-Kathrin (NeuroImage. Clinical, 2017)
The circadian variation of sensory and motor symptoms with increasing severity in the evening and at night is a key diagnostic feature/symptom of the restless legs syndrome (RLS). Even though many neurological diseases have shown a strong nexus between motor and cognitive symptoms, it has remained unclear whether cognitive performance of RLS patients declines in the evening and which neurophysiological mechanisms are affected by the circadian variation. In the current study, we examined daytime effects (morning vs. evening) on cognitive performance in RLS patients (n = 33) compared to healthy controls (n = 29) by analyzing flanker interference effects in combination with EEG and source localization techniques. RLS patients showed larger flanker interference effects in the evening than in the morning (p = .023), while healthy controls did not display a comparable circadian variation. In line with this, the neurophysiological data showed smaller N1 amplitudes in RLS patients compared to controls in the interfering task condition in the evening (p = .042), but not in the morning. The results demonstrate diurnal cognitive changes in RLS patients with intensified impairments in the evening. It seems that not all dopamine-regulated cognitive processes are altered in RLS and thus show daytime-dependent impairments. Instead, the daytime-related cognitive impairment emerges from attentional selection processes within the extra-striate visual cortex, but not from later cognitive processes such as conflict monitoring and response selection.
Keywords: senioři; Circadian Rhythm; EEG; Electroencephalography; Cognition; Restless Legs Syndrome; Restless legs syndrome (RLS); syndrom neklidných nohou; cirkadiánní rytmus; Middle Aged; mužské pohlaví; elektroencefalografie; Adult; kognice; ženské pohlaví; Circadian variation; Humans; Attentional selection; Flanker interference effect; Attention; pozornost; lidé středního věku; dospělí; Female; Aged; lidé; Male